2017
DOI: 10.1177/0961203317742710
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and outcome of systemic lupus erythematosus (SLE) admission rates in a large teaching hospital in sub-Saharan Africa

Abstract: Although it was previously believed that systemic lupus erythematosus was uncommon among Africans, it has become increasingly apparent that the incidence is higher, and socioeconomic challenges such as physician shortages, poor medical facility access, and poor health literacy may worsen prognosis. This retrospective study examines characteristics and outcomes of hospitalized systemic lupus erythematosus patients over a two-year period and serves as a baseline for comparison for future studies to examine the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…15 The main reason for hospitalizations in our SLE patients was disease activity, consistent with what has been reported in other studies worldwide. [16][17][18][19] Renal disease was the leading cause of hospitalization for disease activity, with 37/73 (50.7%) admissions; similar data were found in a study from Colombia, in which 74% of hospitalizations for activity were due to kidney involvement; 17 that was not the case in the above-mentioned 1000 Canadian Faces of Lupus study in which renal activity was the fourth leading cause. This can be explained by the different ethnic composition of patients in these cohorts, as Mestizo patients (European and Amerindian ancestry) are at an increased risk of developing kidney disease.…”
Section: Discussionmentioning
confidence: 58%
“…15 The main reason for hospitalizations in our SLE patients was disease activity, consistent with what has been reported in other studies worldwide. [16][17][18][19] Renal disease was the leading cause of hospitalization for disease activity, with 37/73 (50.7%) admissions; similar data were found in a study from Colombia, in which 74% of hospitalizations for activity were due to kidney involvement; 17 that was not the case in the above-mentioned 1000 Canadian Faces of Lupus study in which renal activity was the fourth leading cause. This can be explained by the different ethnic composition of patients in these cohorts, as Mestizo patients (European and Amerindian ancestry) are at an increased risk of developing kidney disease.…”
Section: Discussionmentioning
confidence: 58%
“…Several Sub-Saharan African case series have identi ed high SLE-related morbidity and mortality due to infections and cardio-renal disease (21,22,39). While epidemiologic studies on the African continent are sparse, individuals of recent African ancestry throughout the diaspora have some of the highest reported incidence and prevalence of SLE (40,41).…”
Section: Apol1 Genotype Is Associated With Case Fatalitymentioning
confidence: 99%
“…For example, a retrospective review showed that SLE represented 5.28/1000 inpatient admissions at Korle bu Teaching Hospital in Accra, Ghana (21). These patients experienced high mortality as 43% died, most commonly of kidney disease, over a two-year period (22). It is unclear how APOL1 high-risk genotype contributes to this trend.…”
Section: Introductionmentioning
confidence: 99%
“…4 describes the study selection process. Table 3 summarizes the characteristics of the overall 15 included studies [[2], [3], [4], [5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16]] whereas Table 4 summarizes only the studies included in the mortality analysis [4,[6], [7], [8], [9],14,16].
Fig.
…”
Section: Data Descriptionmentioning
confidence: 99%